KOMPETENSI DAN INDEPENDENSI DALAM KUALITAS AUDIT AUDITOR : SUATU PENDEKATAN TEORITIS - Minarni A. Dethan (Journal of Management Small and Medium Enterprises (SMEs), 2016)
Public accounting profession (auditors) are like "sword in both eyes,". Auditors should consider thecredibility and ethics of the profession, on the other hand they also cope pressure from clients in avariety of auditing decision. If the auditors are unable to resist the pressure from customers such aspersonal stress, emotional and financial independence of auditors, it will reduce and may affect thequality of the audit. Accordance with its responsibility to increase the reliability of the financialstatements of an accounting firm, public accounting profession not only need to have the skill orexpertise, but also must be independent. To be able to meet quality audit of the auditor in theapplying of his/her profession, he/she should be guided by the code of ethics for accountants,professional standards and applicable accounting standards in Indonesia. Each audit is to maintainthe integrity and objectivity in the performance of their duties to act honestly, firmly, unpretentious,so that it can act fairly, without being influenced of personal interests. The auditors identify andreport violations of the client's accounting system. Violation of measuring the quality of auditfindings related to the knowledge and expertise of the auditor. While encouraging the offensedepends on the auditor to disclose the violation. The reader will depend on the auditor'sindependence instead.Keywords: Competence, Independence and Quality Audit